Favourable long term prognosis in stable angina pectoris: an extended follow up of the angina prognosis study in Stockholm (APSIS) - Hjemdahl, P (BMJ Group, 2006)
OBJECTIVE: To evaluate the long term prognosis of patients with stable angina pectoris. DESIGN: Registry based follow up (median 9.1 years) of patients participating in the APSIS (angina prognosis study in Stockholm), which was a double blind, single centre trial of antianginal drug treatment. PATIENTS: 809 patients (31% women) with stable angina pectoris < 70 (mean (SD) 59 (7) years at inclusion) and an age and sex matched reference population from the same catchment area. INTERVENTIONS: Double blind treatment with metoprolol or verapamil during 3.4 years (median), followed by referral for usual care with open treatment. MAIN OUTCOME MEASURES: Cardiovascular (CV) death and non‐fatal myocardial infarction (MI) in the APSIS cohort and total mortality in comparison with reference subjects. RESULTS: 123 patients died (41 MI, 36 other CV causes) and 72 had non‐fatal MI. Mortality (19% v 6%, p<0.001) and fatal MI (6.6% v 1.6%, p < 0.001) were increased among male compared with female patients. Diabetes, previous MI, hypertension, and male sex independently predicted CV mortality (p < 0.001). Diabetes greatly increased the risk in a small subgroup of female patients. Male patients had higher mortality than men in the reference population during the first three years (cumulative absolute difference 3.8%) but apparently not thereafter. Female patients had similar mortality to women in the reference population throughout the 9.1 years of observation. CONCLUSIONS: Female patients with stable angina had similar mortality to matched female reference subjects but male patients had an increased risk. Diabetes, previous MI, hypertension, and male sex were strong risk factors for CV death or MI.